From Penrose to Sirmon: The Evolution of Resource Based Theory - Diin Fitri, SE., MM.; Rolan Mauludy Dahlan; Samudra Sukardi (Journal of Management and Leadership, 2018)
RBT has grown rapidly and become one of the most important theories in strategic management. This paper examines the development of RBT from the initial concept to several contemporary ideas that have grown rapidly in recent years. The exploration uses literature study approachs. This study is expected to provide a comprehensive overview of the historical roots, definitions, relationships between concepts and the direction of contemporary development. The contemporary direction of RBT leads to the integration of resources orchestration with economic theory, the exploration of the microstructure of RBT and the practical implementation of resources orchestration.